2015
DOI: 10.1111/os.12201
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Repair Technique for Acute Achilles Tendon Rupture with Assistance of Kirschner Wire

Abstract: The aim of this study is to introduce a self-designed, minimally invasive technique for repairing an acute Achilles tendon rupture percutaneously. Comparing with the traditional open repair, the new technique provides obvious advantages of minimized operation-related lesions, fewer wound complications as well as a higher healing rate. However, a percutaneous technique without direct vision may be criticized by its insufficient anastomosis of Achilles tendon and may also lead to the lengthening of the Achilles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…They offered Kirschner wire leverage before suturing for effective recovery of tendon length. 19 Kocaoglu et al evaluated absorbable and non-absorbable sutures for Achilles tendon repair with a suture-guiding device and they found similar functional results with both suture types but less suture reaction with absorbable sutures. 20 Similar to the literature, our results showed that this technique provides patients an early return to work, improved AOFAS and Thermann scores, with minimal risk of complications.…”
Section: Aktas and Kocaoglu Compared Clinical And Functional Results mentioning
confidence: 99%
“…They offered Kirschner wire leverage before suturing for effective recovery of tendon length. 19 Kocaoglu et al evaluated absorbable and non-absorbable sutures for Achilles tendon repair with a suture-guiding device and they found similar functional results with both suture types but less suture reaction with absorbable sutures. 20 Similar to the literature, our results showed that this technique provides patients an early return to work, improved AOFAS and Thermann scores, with minimal risk of complications.…”
Section: Aktas and Kocaoglu Compared Clinical And Functional Results mentioning
confidence: 99%
“…Furthermore, it could introduce the possibility of earlier surgery, facilitating less invasive or percutaneous techniques that are associated with fewer soft tissue complications. 19…”
Section: Discussionmentioning
confidence: 99%
“…This will also aid maintenance of the existing performance for operating on those who require surgical management in a timely manner, as evidenced by the fact 80% of these patients underwent their procedure within two weeks of presentation in 2018, negating the need for more complex and expensive surgical procedures. Furthermore, it could introduce the possibility of earlier surgery, facilitating less invasive or percutaneous techniques that are associated with fewer soft tissue complications [19].…”
Section: P R O O Fmentioning
confidence: 99%
“…Injuries of the sural nerve remain the most described complication in percutaneous approach 19,23,25,33 , having an incidence high up to 16.7% 13 . Since the rst description of percutaneous technique by Ma and Gri th 34 in 1977, many modi cations have been proposed thereafter 18,29,31,35,36,37,38,39 for better vision of pathology and to reduce possible complications. Some were focused to prevent sural nerve damage, for example exposing the nerve 35 , making posterior 18 or paramedial incisions 37 , and placing the knots at the medial aspect of the Achilles tendon 36 .…”
Section: Discussionmentioning
confidence: 99%